Effects of crude protein supplementation during beef cow’s mid-gestation on the cows performance, milk production and metabolism - Galvão, Matheus Castilho (2022)
The aim of this study was to evaluate the effect of protein restriction during the middle third of pregnancy in beef cows and its effect during the postpartum phase of the cows. The experiment was conducted for 2 consecutive years. Forty-three Tabapuã cows (Bos taurus indicus) were used, separated into two treatments: protein restriction (RES; n = 24) and supplemented (SUP; n = 19), treatments were applied from 100 to 200 days of gestation. The restricted group received a basal diet composed of corn silage + sugarcane bagasse. The supplemented group received the same basal diet with protein supplementation (3.5 g/kg BW, ~40% crude protein). From 200 days until calving, the cows were allocated to Brachiaria brizantha cv. Marandu until partum. Milking were carried out at 7, 30, 60, 120 and 210 days postpartum to obtain the milk production of the cows, the milking were done manually right after the application of oxytocin. The milk was weighed, the volume was measured and about 50 ml were sent to a commercial laboratory for analysis of the milk composition and cows and calves were weighed right after milking. At 30 days of lactation, blood samples were collected from the cows, which were later centrifuged, and the plasma separated for analysis of BHBA, NEFA, glucose and BUN. Intake assessment and digestibility assay were performed at 120 and 200 days postpartum. Data were evaluated using PROC MIXED from SAS, considering maternal treatment, calf sex and their interaction as fixed effect and year as random. Cows of treatment SUP were 11% heavier at 7 and 30 days postpartum when compared to RES cows (P < 0.05), however, this difference was not maintained throughout lactation. Milk production of SUP cows was 23% higher than RES cows at 7 days of lactation (P < 0.05), this difference was not maintained throughout lactation (P > 0.05). There was no significant difference for milk intake, digestibility and composition during lactation (P > 0.05). In conclusion, the use of protein supplementation in the middle third of pregnancy resulted in an improvement in the milk production of cows in early lactation, however, this difference disappeared over time.